Implementation of Village Fund Allocation for Development of Tumbit Dayak Village - Sambaliung District, Berau Regency (East Kalimantan Province) - Sofyan, Edwin; Amin, Muh. Jamal; Setiani, Made Yudhi (Technium Social Sciences Journal, 2021)
The Village Fund Allocation (ADK) brings fresh air, which is expected to further revitalize the village in the future. This research point discusses how the implementation, supporting factors, and inhibiting factors of ADK in 2018 in infrastructure development in Tumbit Dayak Village. This research is descriptive based, which seeks to describe, describe, and report an actual event. Primary data, where we interviewed several related elements based on the Tumbit Dayak Village Regulation Number 05 of 2018 concerning the Village Revenue and Expenditure Budget, support the data source. Under the topic, the implementation model of ‘Edward III’s policy’ is the fundamental basis. An interesting finding is shown by implementing the ADK policy in Tumbit Dayak Village that has not run optimally. In fact, the main aim of the ADK policy has not been realized optimally. Only in the village administration sector has achieved through ADK. To make up for other vital programs and the minimal ADK budget, the community works together to improve the capacity of community institutions.